Taf'īl Kitāb Ādab al-'Ālim Wa al-Mut'allim Fī Ta'allum al-Lughah al-'Arabiyyah Litarqiyah Dāfi'iyyah al-Mu'allim Wa al-Muta'allim - Basit, Abdul; Syafei, Isop (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Purpose- This research aims to find out how to increase the motivation of teachers and students at MI Islamiyah Sawojajar through the actualization of the book Adab 'Alim wa Muta'llim in learning Arabic. Design/Methodology/Approach- The research method used in this research is descriptive qualitative.  Researchers act as the main instrument, namely researchers who create data collection instruments such as researchers creating interview questions, observation instruments and document data instruments. The data collection techniques are observation, interviews and documentation which are then reduced and verified and then presented. Findings— Research on the Actualization of the Book of Adab 'Alim wa Muta'llim in Arabic Language Learning to Increase Teacher and Student Motivation produced data in the form of increased motivation in learning Arabic for both teachers and students in accordance with the contents of the book Adab 'Alim wa Muta'llim with details ; for teachers: 1) Professional (B>>A), 2) Initiative (A>>A), 3) Prioritizes teaching tasks (B>>A), 4) Likes to increase knowledge (B>>A) and 5) No easily complacent (C>>B). For students: 1) Desire to succeed (B>>A), 2) Encouragement to learn (B>>A), 3) Hope and aspirations (C>>B), 4) Reward for learning (B>>A) , 5) Attraction of learning (C>>A) and 6) Conducive learning situation (B>>A). Research Limitation/Implications- Due to limited time, this research was carried out once but was still able to produce valid and reliable data which represents the research objectives.